Levels and trends in key socioeconomic inequalities in childhood undernutrition in Ethiopia: evidence from Ethiopia demographic and health surveys 2000-2019 - Negussie Shiferaw; Nigatu Regassa (Springer, 2023)
Abstract Introduction The global burden of childhood undernutrition is mainly concentrated in low-income and lower-middle-income countries. In Ethiopia, childhood undernutrition varies significantly across different population groups. The present study is aimed at examining the levels and trends in key socioeconomic inequalities in childhood undernutrition in Ethiopia. Methods This cross-sectional study was based on a total pooled sample of 48,782 under-five children drawn from five rounds of the Ethiopia Demographic and Health Surveys (2000-2019). We used multilevel binary logistic regression analysis to determine the key socioeconomic determinants of undernutrition among under five children. In addition, we applied concentration index and decomposition rate analysis techniques to explore the levels and trends in key socioeconomic inequalities in childhood undernutrition. Results Place of residence, household wealth status (approximated by asset-based wealth index), and maternal education, among others, were the key socioeconomic variables significantly associated (p < 0.001) with childhood undernutrition in Ethiopia. The level of inequality was the highest with children from rural areas, poor households and uneducated mothers. Absolute socioeconomic inequality in childhood undernutrition prevalence rate was declined by 9.72 during the study period (2000 to 2019). Conclusion Childhood undernutrition was unequally distributed among under-five children in Ethiopia, and largely concentrated among low socioeconomic status population groups. The identified key socioeconomic drivers of inequality in childhood undernutrition can be used to inform localized interventions and communication strategies to improve nutritional status of under-five children in Ethiopia. The study underscores development of poverty reduction strategies that directly address the existing challenges of the food insecurity and childhood undernutrition for the low-income population groups in the country.